2010
DOI: 10.1111/j.1708-8240.2010.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bleaching Agents on Surface Roughness of Sound or Eroded Dental Enamel Specimens

Abstract: Bleaching agents with a high concentration of peroxide or an acidic pH can influence the surface roughness of sound or eroded enamel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 26 publications
5
42
0
10
Order By: Relevance
“…Bistey and colleagues reported that some bleaching agents have a lower than ideal pH, which may cause alterations in the mineral content of enamel, contributing to the formation of depressions that are not very deep, with an increase in enamel porosity, promoting slight erosion. In the same way as Azrak and colleagues who affirmed that the radicals released and low pH values of gels are considered causers of tissue damage. In the present study, 35% hydrogen peroxide with calcium presented the highest pH value (pH = 8.76), while the 7.5% hydrogen peroxide without calcium presented the lowest pH value (pH = 6.69).…”
Section: Discussionmentioning
confidence: 99%
“…Bistey and colleagues reported that some bleaching agents have a lower than ideal pH, which may cause alterations in the mineral content of enamel, contributing to the formation of depressions that are not very deep, with an increase in enamel porosity, promoting slight erosion. In the same way as Azrak and colleagues who affirmed that the radicals released and low pH values of gels are considered causers of tissue damage. In the present study, 35% hydrogen peroxide with calcium presented the highest pH value (pH = 8.76), while the 7.5% hydrogen peroxide without calcium presented the lowest pH value (pH = 6.69).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study agree with those of previous investigations, which did not find alterations in surface roughness induced by in‐office or at‐home whitening agents. However, other investigations revealed increase or decrease in enamel surface roughness after tooth whitening due to the oxidative and erosive actions of the whitening agents. Nevertheless, Sulieman et al who focused on the safety concerns with whitening procedures by investigating the effects of a high concentration H 2 O 2 in‐surgery whitening product on enamel, concluded that studies which reported adverse effects on enamel reflect not the whitening agent itself but the pH of the formulation used.…”
Section: Discussionmentioning
confidence: 96%
“…A literatura já evidenciou que os agentes clareadores são capazes de afetar de forma similar tanto as superfícies dentárias humanas quanto as bovinas. Dessa forma, dentes bovinos podem substituir eficazmente os dentes humanos nas pesquisas odontológicas sendo o seu uso seguro independente das técnicas e materiais clareadores utilizados 16,21 . No estudo de Lia Mondelli et al 2 (2015), ao avaliar a microdureza em esmaltes bovinos após o clareamento, os autores puderam constatar que apenas em um grupo de amostra não havia acontecido alterações nas primeiras 24 horas.…”
Section: Discussionunclassified
“…Já pesquisadores como Azrak et al 21 (2010) atribuíram a frequência e ao tempo de exposição do esmalte a produtos clareadores, às desmineralizações dentárias. Esses achados poderiam explicar os resultados dessa pesquisa quando o G2, grupo em que as amostras foram submetidas ao clareamento por mais tempo, apresentou a maior rugosidade superficial dos dentes clareados 23,17 .…”
Section: Discussionunclassified